Targeting Tristetraprolin Expression or Functional Activity Regulates Inflammatory Response Induced by MSU Crystals - lv, Linxi; Qin, Ting; Huang, Qiushi; Jiang, Hui; Chen, Feng; Long, Fan; Ren, Long; Liu, Jianpin; Xie, Yongen; Zeng, Mei (Frontiers in Immunology, 2021)
The RNA-binding protein tristetraprolin (TTP) is an anti-inflammatory factor that prompts the mRNA decay of target mRNAs and is involved in inflammatory diseases such as rheumatoid arthritis (RA). TTP is regulated by phosphorylation, and protein phosphatase 2A (PP2A) can dephosphorylate TTP to activate its mRNA-degrading function. Some small molecules can enhance PP2A activation. Short interfering RNA (siRNA) targeting TTP expression or PP2A agonist (Arctigenin) was administered to monosodium urate (MSU) crystal-induced J774A.1 cells, and the expression of inflammatory related genes was detected by RT-PCR and Western blot assays. The effects of Arctigenin in mouse models of acute inflammation induced by MSU crystals, including peritonitis and arthritis, were evaluated. The data indicated that TTP expression levels and endogenous PP2A activity were increased in MSU-crystal treated J774A.1 cells. TTP knockdown exacerbated inflammation-related genes expression and NLRP3 inflammasome activation. However, PP2A agonist treatment (Arctigenin) suppressed MSU crystal-induced inflammation in J774A.1 cells. Arctigenin also relieved mitochondrial reactive oxygen species (mtROS) production and improved lysosomal membrane permeability in MSU crystal-treated J774A.1 cells. Moreover, TTP knockdown reversed the anti-inflammatory and antioxidant effects of Arctigenin. Oral administration of Arctigenin significantly alleviated foot pad swelling, the number of inflammatory cells in peritoneal lavage fluids and the production of IL-1β in the mouse model of inflammation induced by MSU crystals. Collectively, these data imply that targeting TTP expression or functional activity may provide a potential therapeutic strategy for inflammation caused by MSU crystals.